The impact of money supply and interest rates on the rupiah exchange rate in Indonesia (2015–2024) - Septri Anisa; Andreas Panjaitan; Artha Putri Br Karo; Debora Silvia Hutagalung (Economic: Journal Economic and Business, 2026)
Fluctuations in the rupiah exchange rate reflect the dynamics of macroeconomic conditions and monetary policy responses to domestic and global pressures. This study aims to analyze the influence of the money supply and interest rates on the rupiah exchange rate from 2015 to 2024. A quantitative approach was used, utilizing annual time series data and linear regression analysis to identify the relationship between variables. The results indicate that the money supply has a positive and significant effect on the exchange rate, reflecting that increases in domestic liquidity are followed by changes in the exchange rate. Conversely, interest rates do not show a statistically significant effect. This finding confirms that liquidity plays a more dominant role than interest rates in influencing the exchange rate. Therefore, controlling the money supply is a crucial aspect in maintaining exchange rate stability.